METHODOLOGY OF WRITTEN SPEECH DEVELOPMENT (TAMADDUN NURI JURNALI, 2024)
The article describes the method of developing students' written speech.  The main requirement for the mother tongue textbook is to improve students' oral and written literacy, to teach them to speak correctly and fluently. Clear and fluent speech and the correct use of grammatical devices are necessary for the correct formation of written speech. Good knowledge of grammatical devices helps the child to construct sentences correctly and write without any mistakes. The formation of writing skills is further developed through exercises. The article provides detailed information about this.